Paper Review Text Mining Twitter - Samuel Dananjaya Raharjo; Gunawan Wang (Budapest International Research and Critics University, 2022)
Research on data analysis from social media such as Twitter has been carried out in recent years. This cannot be separated from the fact that Twitter is one of the most popular social media used by social-networkers. One of the services provided by Twitter is an API (Application Programming Interface) which allows developers to get Twitter data directly for further processing. This paper aims to review the papers on twitter data mining that have been published. The contribution of this paper is to provide information on the extent of the research that has been done on Twitter data mining to obtain a mapping that will be used as the next research plan. This review paper does not choose the best technique or method and does not provide an opinion on an analysis that has been carried out from previous research. From this review paper, it can be seen that a research activity can be carried out using twitter text data, with data acquisition techniques and text analysis methods in a text mining approach.